Potential nephrotoxic effects of exposure to silver. Issue 4 (April 1987) - Rosenman, K D; Seixas, N; Jacobs, I
Abstract : A cross sectional study was conducted on workers engaged in manufacturing precious metal powder. Of the 27 workers, 96% had raised urine silver concentrations (range 0.5-52.0 micrograms/l, mean 11.3 micrograms/l) and 92% had raised blood silver concentrations (range 0.05-6.2 micrograms/100 ml, mean 1.0 microgram/100 ml). Nineteen per cent also had raised urine cadmium concentrations (range 1.9-76.0 micrograms/l, mean 11.8 micrograms/l). Most workers had symptoms of respiratory irritation and nose bleeds were reported in eight (30%) of the 27 workers. Deposition of silver in the cornea of the eye was detected in five of eight (63%) of the long term workers. Although not statistically significant, corneal deposition was associated with complaints of decreased night vision. The urinary enzyme N-acetyl-B-D glucosaminidase (NAG) was significantly raised in four individuals and was correlated with blood silver concentrations and age. In addition, the group's average NAG concentration was significantly higher than that found in a control population. No association between age and urinary NAG was found in the control group. Estimated creatinine clearance was also significantly lower in the group exposed to silver than in the control group. Kidney function appears to have been adversely affected by exposures at work but because of the exposure to cadmium the role of silver in causing the decrement in kidney function could not be definitely determined.